1998
DOI: 10.1017/s0260305500014634
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory experiments on shear failure of snow

Abstract: ABSTRACT. Using a direct simple-shear apparatus, snow samples (llS mm in diameter, 16~ 18 mm in height) taken from a so-called homogeneous layer (small rounded particles, density: 290 kg m -3) were tes~ed in a cold laboratory. Experiments were performed for strain rates between 7 x lQ-6 s-I and 5 x lQ-3 s lat test temperatures of ~5°C, ~ IO D C and ~ 15 D C. The efiects of strain rate and temperature on failure stress, failure strain, stiffness (initial tangent modulus ) and toughness were studied. The transit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
70
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(78 citation statements)
references
References 6 publications
7
70
1
Order By: Relevance
“…Therefore, various studies on shear failure of homogeneous snow samples under controlled laboratory conditions have been performed (e.g. Schweizer, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, various studies on shear failure of homogeneous snow samples under controlled laboratory conditions have been performed (e.g. Schweizer, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, we test the hypothesis that different timescales of fracturing and sintering of bonds explain the strain-rate dependence of the failure behaviour of snow (Schweizer, 1999). We use experimental results of snow under shear deformation (Schweizer, 1998) for comparison with our model output.…”
Section: Introductionmentioning
confidence: 99%
“…, an unusually large value in snow characterizing the fracture as a brittle failure [Narita, 1980] and implying very low material strength of the disturbed weak layer [McClung, 1977;Narita, 1980;Fukuzawa and Narita, 1992;Schweizer, 1998]. …”
mentioning
confidence: 99%
“…Second, we consider the dependence of τ c on T ss . Foehn et al (1998) and Schweizer (1998) observed that τ c depends both on the snow temperature and on the applied shear rate. For our Herschel-Bulkley flow, τ c is the threshold stress for failure of the plug at z = h where the shear rate dv/dz vanishes (note that, under our experimental conditions, this transition from shear flow to plug flow might not be perfectly smooth).…”
Section: Model Parametersmentioning
confidence: 99%